A Multi-Criteria Decision-Making Framework for Evaluating Government Institutional Performance: The Role of Corporate Citizenship in Hajj Fund Ecosystems - Eko Surya Lesmana; Adi Zakaria Afiff; Setyo Hari Wijanto; Rahmatina Awaliah Kasri (Decision Making: Applications in Management and Engineering, 2025)
This study explores the influence of corporate citizenship—defined as an organisation’s responsibility to adhere to legal obligations and meet societal expectations—on the performance of public sector institutions. The investigation considers the mediating roles of knowledge mobility, innovation appropriability management, network stability, and the development of innovation value propositions. A quantitative approach is employed, utilising Multi-Criteria Decision-Making (MCDM) techniques to prioritise the critical success factors impacting institutional performance within the Hajj fund management ecosystem. Data were obtained through a structured questionnaire administered to 81 respondents involved in Indonesia’s Hajj fund management, encompassing decision-makers from Islamic financial institutions, zakat agencies, and associated investment stakeholders. The data analysis was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM). To strengthen the decision-making framework, the study integrates the Analytic Hierarchy Process (AHP) as an MCDM instrument to assess and rank the components of corporate citizenship—namely legal, ethical, discretionary, and economic dimensions—against ecosystem orchestration variables, including knowledge mobility, network stability, and innovation value propositions. The findings underscore that the effectiveness of corporate citizenship is substantially linked to the performance of public institutions, primarily through its impact on knowledge mobility and innovation value creation. The results suggest that corporate citizenship, understood as both organisational conduct and practice, along with knowledge mobility, may serve as pivotal drivers of institutional performance, particularly within the domains of corporate governance and public sector administration. The application of MCDM offers a robust, evidence-based mechanism to guide strategic decisions related to resource allocation, innovation initiatives, and integrated stakeholder coordination within public sector ecosystems that prioritise non-profit objectives. As a quantitative inquiry, the research aims to elucidate the determinants of institutional performance in government settings. Future studies may enrich these insights through qualitative methodologies, such as interviews or case study analyses. Additionally, the exploration of combined decision-support systems (DSS) incorporating MCDM frameworks may prove valuable when applied to ecosystem governance in broader public sector environments. This research makes several novel contributions to both theory and practice. It provides empirical evidence supporting the application of the ecosystem orchestration model in a government context, specifically within the management of Hajj funds in accordance with Sharia principles. The study posits that implementing such a model, where a central entity exerts normative influence over a diverse array of institutional partners, is grounded in practical application. Furthermore, the model accommodates a hybrid structure involving both profit-oriented and non-profit actors. The originality of the research is also evident in its use of quantitative decision modelling, specifically through MCDM-based DSSs, which enable structured, sequential, and evidence-driven decision-making processes aimed at improving institutional performance within complex, multi-stakeholder public sector ecosystems. To the authors’ knowledge, this represents the first scholarly examination of the link between corporate citizenship and public institutional performance through the lens of MCDM models and DSSs.